Eksperimen Pembelajaran Matematika Dengan Problem Based Learning Dan Problem Based Instruction Terhadap Prestasi Belajar Ditinjau Dari Keaktifan Siswa Kelas VII SMP Negeri 1 Colomadu Tahun 2015/2016 - Kurniawan, Ajib Candra; , Dr.Sumardi,M.Si (2016)
The aim of research to describe and analyze: (1) the influence of mathematics learning with PBL and PBI on the learning achievement, (2) the effect on the student's activeness learning achievement, (3) the interaction between the learning strategies and student activeness on learning achievement. Thekind of this research is an experiment with quasi-experimental design. The research population was all students of class VII SMP N 1 Colomadu on the second semester of the 2015/2016 academic year. The study sample consisted of two classes. The sampling technique using cluster random sampling. The test method usage data collection and documentation. Data were analyzed by analysis of variance with two different cell lines. The results of the data analysis with a significance level of 5% was obtained: (1) there is an influence of PBL and PBI on the learning achievement of mathematics, with FA = 24,134 (2) there are significant involvement of the student's learning achievement, with FB = 13,427 (3) There is no Interaction betweenPBL and PBI on student activeness with the learning achievement, with FAB = 2,005. Keyword: Learning achievement, PBI, PBL, Student's Activeness